Asosiasi antara Indeks Massa Tubuh dan Mortalitas pada Pasien Gagal Ginjal Kronis yang Menjalankan Hemodialisa Reguler: Meta-analisis dari Studi Kohort - Latupeirissa, Joue Abraham Trixie; Sudaryo, Mondastri Korib; Gabriella, Dorothy, Ms.; Suryandari, Benedikta, Ms.; Putri, Vine Aprilianita Sri Indah, Ms. (UI Scholars Hub, 2024)
Chronic kidney failure patients must undergo hemodialysis for life, therefore it is important to maximize hemodialysis services in every health facility. Accordingly, factors related to survival rates must be addressed. One of them is low Body Mass Index (BMI). This study assessed the relationship between low BMI and mortality in the patients. The study design used was meta-analysis. The articles involved were in the period 2012 - 2024. There are three literature sources: medical databases, previous studies, and ongoing research. Overall, 26 articles were obtained. Data analysis showed that BMI